Foot Care among Diabetes Patients: A Concept Analysis - Parliani Parliani; Somporn Rungreangkulkij; Khanitta Nuntaboot (Nurse Media Journal of Nursing, 2023)
Background: The concept analysis of “foot care” is essential for expanding the nursing knowledge base, synthesizing a broader theoretical concept, and guiding more effective care for diabetes patients with and without diabetic foot ulcers (DFU). Foot care in nursing has not yet been comprehensively defined for nurses and other healthcare professionals.Purpose: This concept analysis aimed to elucidate the nursing practice concept of foot care. The study identified surrogate terms associated with the concepts, attributes, antecedents, and consequences by employing Rodger’s evolutionary method in a critical analysis of the relevant literature.Methods: This research used Rodger’s evolutionary analysis. The databases were PubMed (n=188), ProQuest (n=4,790), ScienceDirect (n=292), and Google Scholar (n=7,810) with a total of 13,080 articles identified in this study. The screening process involved evaluating titles and abstracts, followed by a thorough analysis of inclusion criteria, which included full-text articles and the presence of keywords: foot care, diabetes, diabetic foot ulcer. Articles that did not provide a clear definition of foot care were excluded. A total of 45 articles were included. Rodger’s evolutionary analysis stressed inductive investigation and careful analysis of the concept.Results: The results of the foot care concept analysis were: (1) among people with diabetes without DFU, the attributes were foot screening and foot examination, while the antecedents were high glycemic levels, inability of the pancreas to produce insulin, abnormal foot skin condition, and foot-related behaviors; (2) among patients with DFU, the attributes were foot intervention and education, while the antecedents included foot self-care knowledge, motivation, and family and social support. The consequences associated with the concept of foot care included improvement in self-efficacy, quality of life, and self-care behavior.Conclusion: Nurses can use the findings of this foot care analysis in their clinical work by promoting and practicing foot care as a preventative measure that shields patients from ulcers. Additionally, nurses can intervene when patients already have ulcers and provide appropriate wound care. Foot examinations become more manageable when specific practice guidelines are available for diabetes patients.